Imagination Reduces False Memories for Everyday Action Sentences: Evidence From Pragmatic Inferences - Maraver, María J.; Lapa, Ana; Garcia-Marques, Leonel; Carneiro, Paula; Raposo, Ana (Frontiers in Psychology, 2021)
Human memory can be unreliable, and when reading a sentence with a pragmatic implication such as “the karate champion hit the cinder block”, people often falsely remember that the karate champion “broke” the cinder block. Yet, research has shown that encoding instructions affect the false memories we form. On the one hand, instructing participants to imagine themselves manipulating the to-be-recalled items increases false memories (imagination inflation effect). But on the other hand, instructions to imagine have reduced false memories in the DRM paradigm (imagination facilitation effect). Here we explored the effect of imaginal encoding with pragmatic inferences, a way to study false memories for information about everyday actions. Across two experiments, we manipulated imaginal encoding through the instructions given to participants and the after-item filler task (none vs. math operations). In Experiment 1, participants were either assigned to the encoding condition of imagine + no filler; pay attention + math; or memorize + math. In Experiment 2, the encoding instructions (imagine vs. memorize) and the filler task (none vs. math) were compared across four separate conditions. Results from the two experiments showed that imagination instructions lead to better memory, by showing a higher proportion of correct responses and better performance in a memory benefit index. Similarly, a significant reduction of false memories was observed across both experiments, even though a complementary Bayesian analysis only supported this conclusion for Experiment 1. The findings show that imaginal encoding improves memory, suggesting the engagement of a distinctiveness heuristic and source-monitoring process.